Amazon product reviews sentiment analysis using supervised learning algorithms - Hawladar, Mohibullah; Ghosh, Arjan; Raad, Zaoyad Khan; Chowdhury, Wali Ahad; Shehan, Md Sazzad Hossain (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.